Capital Adequacy Ratio, Loan to Deposit Ratio, Ukuran Perusahaan dan Return On Assets dengan Non Performing Loan sebagai Variabel Pemoderasi - Anggawulan, Made Diah Dianti; Suardikha, I Made Sadha (E-Jurnal Akuntansi, 2021)
This study aims to examine how CAR, LDR, and firm size influence ROA with NPL as a moderating variable. The location of the study was conducted at the Indonesia Stock Exchange (IDX) through its official website www.idx.co.id with a population of 43 companies that are on the Indonesia Stock Exchange in 2017. Purposive sampling technique was used in the determination of the sample in this study, so as to obtain a research sample of 39 banking. Analysis of the data used is the MRA (Moderated Regression Analysis) test. According to the result of the analysis it was found that CAR LDR, NPL, and firm size do not have an influence on ROA. NPL cannot moderate CAR, LDR, and firm size to ROA. Keywords:  CAR; LDR; NPL; Firm Size; ROA.